2005
DOI: 10.1038/sj.npp.1300937
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar Vermis Involvement in Cocaine-Related Behaviors

Abstract: Although the cerebellum is increasingly being viewed as a brain area involved in cognition, it typically is excluded from circuitry considered to mediate stimulant-associated behaviors since it is low in dopamine. Yet, the primate cerebellar vermis (lobules II-III and VIII-IX) has been reported to contain axonal dopamine transporter immunoreactivity (DAT-IR). We hypothesized that DAT-IR-containing vermis areas would be activated in cocaine abusers by cocaine-related cues and, in healthy humans, would accumulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
71
2
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(82 citation statements)
references
References 74 publications
6
71
2
3
Order By: Relevance
“…Neuroimaging findings showed that presenting cocaine addicts with visual or auditory cues resulted in greater activity in the anterior and posterior vermis (Anderson et al, 2006). In the same way, widespread activation of the vermis and cerebellar hemispheres was found when drug users were exposed to tactile marijuana cues (a pipe) (Filbey et al, 2009).…”
Section: The Cerebellum In Cravingmentioning
confidence: 87%
See 4 more Smart Citations
“…Neuroimaging findings showed that presenting cocaine addicts with visual or auditory cues resulted in greater activity in the anterior and posterior vermis (Anderson et al, 2006). In the same way, widespread activation of the vermis and cerebellar hemispheres was found when drug users were exposed to tactile marijuana cues (a pipe) (Filbey et al, 2009).…”
Section: The Cerebellum In Cravingmentioning
confidence: 87%
“…Interestingly, the vast majority of human imaging studies in which the cerebellum has been found to be active when craving is experienced were done by exposing addicts to drug-associated cues (Grant et al, 1996;Bonson et al, 2002;Kilts et al, 2001;Anderson et al, 2006;Filbey et al, 2009;Smolka et al, 2006;Tomasi et al, 2015). Similarly, animal research has demonstrated the selective activation of the cerebellum in rodents that express a preference towards cocaine-related cues (Carbo-Gas et al, 2014ab).…”
Section: The Cerebellum In Cravingmentioning
confidence: 99%
See 3 more Smart Citations